Development Of A New Method To Measure The Creep Behavior Of Rubber With The Addition Of Bentonite Based On Scanner-Based Image Processing - Tan, Wai Yee (Universiti Sains Malaysia, 2018)
Creep test is important to determine the amount of strain a specimen can withstand under pressure to identify the suitability of this material to certain application. There are several methods that are used to measure rubber creep such as uniaxial tensile creep measurement apparatus, digital image correlation (DIC) and through the assessment by a 3D Neural Network Reconstructor using bulge testing. The purpose of this research is to develop a new method to measure the creep behavior of rubber with the addition of bentonite of various loading based on scanner-based image processing method. A mask was fabricated and markers were created on the gage length of rubber specimen. A flatbed scanner was used for image acquisition. The scale factor is 0.0423 mm/pixel. A validation experiment was carried out to ensure that the MATLAB algorithm developed is accurate. Spacers used to apply strain during validation test were prepared. The measured strain values were compared with the applied strain values to determine the percentage error. Calibration equations were inserted in the algorithm to remove systematic error. Tensile test was carried out to determine the suitable constant load that should be applied during creep test. Lastly, the creep test was carried out on rubber specimen with different bentonite loadings (0, 10, 30, 50 and 70 phr). The results show that bentonite loading increases the creep resistance of rubber specimen. The findings from this research indicated the capability of the method developed to investigate the creep behavior of rubber based on scanner-based image processing method.